Profil dan Kontribusi Ibn Sa‘d dalam Kajian Hadis Sîrah - Nirwana, Dzikri (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2013)
Historically, the study of hadith in Islam emerged as the study of sîrah. Both of these disciplines appear as awareness and concern of the classical Muslim scholars to the purity and preservation of the historical mission of the Prophet Muhammad. The contribution of hadith to the formation of Islamic historiography in general, is not only just limited to the provision of material which is enormous for writing sîrah, but also has implications for the formation of Islamic historiography writing methods, such as the method isnâd as a character of hadith expert, and the chronological method as the character of historians. Al-Tabaqât al-Kabîr by Ibn Sa‘d (w. 230 H.) is considered as a pioneering work that elaborates on two systems. Even when viewed as an integrative, the works of Ibn Sa‘d regarded as the only one pioneering work who elaborates three forms of historiography at once (sîrah, maghâzî, and asmâ’ al-rijâl). Collaborative forms of Islamic historiography in the works of Ibn Sa‘d is certainly a new breakthrough in the classical historiography art which is in previously only in fragmentary form.